EP480 The impact of gene-specific germline pathogenic variants on clinical presentation of endometrial cancer in Lynch syndrome. (1st November 2019) - Bogani, G; Chiappa, V; Ditto, A; Raspagliesi, F
Abstract : Introduction/Background: Lynch syndrome (LS) is a well know risk factor for developing endometrial carcinoma (EC). Here, we aimed to investigate the impact of gene-specific germline pathogenic variants on clinical features of EC. Methodology: This is a retrospective case series of consecutive surgically-treated patients with histological diagnosis of EC and with a germline pathogenic variant in mismatch repair genes. Classes of risk are graded per the ESGO-ESGO-ESTRO guidelines. Results: Overall, 68 patients with EC and LS were evaluated. Ten (14.7%) patients were excluded due to absence of clear information about the gene involved in LS, thus leaving 58 (85.3%) patients available for the final analysis. MLH1, MSH2 and MSH6 pathogenic variants were observed in 19 (32.7%), 33 (56.9%) and 6 (10.3%) cases, respectively. Mean (SD) age at EC diagnosis was 51 (±6.4), 43.5 (±7.4) and 60.3 (±8.8) years (p=0.0002). Prevalence of non-endometrioid EC were 15.7%, 24.2% and 0% in MLH1, MSH2 and MSH6 group, respectively (p=0.345). Focusing on classes of risk we observed that patients harboring a MLH1 or MSH2 pathogenic variant were at higher risk than patients with a MSH6 mutation. In fact, according to the ESMO-ESGO-ESTRO classification, low, intermediate, and high risk EC accounted in 47.3%, 10.5% and 42.1% of MLH1 group, in 57.6%, 3% and 39.4% of MSH2 group and in 50%, 50% and 0% of MSH6 group (p=0.009). Conclusion: Patients with MLH1 and MSH2 pathogenic variants are at a higher risk of early onset of EC and are characterized by more aggressive disease than patients with MSH6 pathogenic variants. Disclosure: Nothing to disclose.